Interactions between daily abstinence plans and approach/avoidance motivation on cigarette smoking in pre-quit smokers - Loftus, Paddy; Wang, Shirlene D; Pang, Raina D; Kirkpatrick, Matthew G (Experimental and clinical psychopharmacology, 2022)
Enhancing motivation to quit among smokers who are not ready for cessation is a key component of several interventions. However, there is a dearth of empirical data about motivational factors and smoking behavior among pre-quit smokers. Here, we examined interactions between approach/avoidance goal motivations and daily abstinence plan (i.e., plans to either continue or abstain from smoking) on daily cigarette use. Current smokers ( = 82; M = 11.4 cigs/day; 46% Female) completed a baseline assessment, including a measure of approach/avoidance motivation [Behavioral Inhibition and Behavioral Activation Scales (BIS/BAS)], followed by 28-days of Ecological Momentary Assessment (EMA). EMA included a morning assessment of abstinence plan, and evening assessment of cigarettes smoked. Multilevel linear models tested interactions between BIS/BAS and abstinence plan on cigarette smoking (defined as percent change from within-subject mean). There was a significant abstinence plan × BIS interaction, F(1, 637) = 6.567, = .011, and abstinence plan × BAS interaction, F(1, 637) = 6.553, = .011, on cigarette smoking. High BIS and low BAS were each associated with reduced smoking on abstinence days and increased smoking on non-abstinence days. Modest rates of smoking cessation may be due to the unassisted, spontaneous nature of most quit attempts. Among pre-quit smokers, high behavioral inhibition and low behavioral activation may underlie the ability to intentionally vary smoking levels according to individuals' daily abstinence plans. Future studies should examine how motivational factors during the pre-quit stage may predict long-term smoking cessation in the future. (PsycInfo Database Record (c) 2022 APA, all rights reserved).